Ensino de História em cursinhos populares: um estudo sobre o currículo da rede Emancipa SP Guarulhos 2019 - Lima, Cibele De Camargo [UNIFESP] (2019)
This study investigated the curriculum design practices in History at the so-called cursinhos populares (preparatory courses targeted at low income students who want to take the Brazilian university entrance exam) at Rede Emancipa (“Emancipate Network”), a network for low income student’s education that is identified with the pedagogy for liberation. The researcher’s concern was to understand how the History contents were developed in classes taught at the course considering the pressure for teaching introductory subjects as a preparation for university entrance examinations while, at the same time, being aligned with the idea of a liberating type of teaching. For this analysis, theoretical references by Paulo Freire, Ivor Goodson, and Circe Bittencourt, among others, were used.